Exploration of Students' Mathematics Concept Understanding Ability on Social Arithmetic Material in Terms of Gender Differences - Mutiara Hisda Mahmudah; Dini Wardani Maulida; S Sukimin; Muhammad Noor Kholid (Universitas Muhammadiyah Surakarta, 2025)
Concept understanding allows students to relate existing knowledge to new information or situations, so that they can represent mathematical ideas in various forms, both verbally, visually, and symbolically. This study aims to describe the effect of gender differences on students' mathematical concept understanding ability in social arithmetic material in junior high school. The research method used was qualitative with a case study approach, involving 22 seventh-grade students who were selected voluntarily. Data were collected through observation, tests, document analysis, and in-depth interviews, then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results showed that male students tend to rely more on logic and reasoning in solving problems, while female students are more analytical but sometimes less optimal in mathematical representation. Nevertheless, both gender groups were able to fulfill the indicators of concept understanding, such as restating concepts, classifying objects, and applying concepts, although with different approaches. These findings indicate the importance of considering gender differences in designing inclusive and effective mathematics learning strategies. In addition, this study provides important implications for the development of gender-responsive learning strategies to improve students' conceptual understanding.